Risk and causes of paediatric hospital-acquired bacteraemia in Kilifi District Hospital, Kenya: a prospective cohort study. - Aiken, A; Mturi, N; Njuguna, P; Mohammed, S; Berkley, J; Mwangi, I; Mwarumba, S; Kitsao, B; Lowe, B; Morpeth, S; Hall, A; Khandawalla, I; et al. (2011)
BACKGROUND: In sub-Saharan Africa, community-acquired bacteraemia is an important cause of illness and death in children. Our aim was to establish the magnitude and causes of hospital-acquired (nosocomial) bacteraemia in African children. METHODS: We reviewed prospectively collected surveillance data of 33,188 admissions to Kilifi District Hospital, Kenya, between April 16, 2002, and Sept 30, 2009. We defined bacteraemia as nosocomial if it occurred 48 h or more after admission. We estimated the per-admission risk, daily rate, effect on mortality, and microbial cause of nosocomial bacteraemia and analysed risk factors by multivariable Cox regression. The effect on morbidity was measured as the increase in hospital stay by comparison with time-matched patients without bacteraemia. FINDINGS: The overall risk of nosocomial bacteraemia during this period was 5·9/1000 admissions (95% CI 5·2-6·9) but we recorded an underlying rise in risk of 27% per year. The incidence was 1·0/1000 days in hospital (0·87-1·14), which is about 40 times higher than that of community-acquired bacteraemia in the same region. Mortality in patients with nosocomial bacteraemia was 53%, compared with 24% in community-acquired bacteraemia and 6% in patients without bacteraemia. In survivors, nosocomial bacteraemia lengthened hospital stay by 10·1 days (3·0-17·2). Klebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Acinetobacter spp, group D streptococci, and Pseudomonas aeruginosa accounted for three-quarters of nosocomial infections. Nosocomial bacteraemia was significantly associated with severe malnutrition (hazard ratio 2·52, 95% CI 1·79-3·57) and blood transfusion in children without severe anaemia (4·99; 3·39-7·37). INTERPRETATION: Our findings show that although nosocomial bacteraemia is rare, it has serious effects on morbidity and mortality, and the microbiological causes are distinct from those of community-acquired bacteraemia. Nosocomial infections are largely unrecognised or undocumented as a health risk in low-income countries, but they are likely to become public health priorities as awareness of their occurrence increases and as other prominent childhood diseases are progressively controlled. FUNDING: Wellcome Trust.